Eating disorder factors among female school-going adolescents in Jeddah, Saudi Arabia - Almutairi, Reem Saad M (2022)
Background: Eating disorders are characterized by an abnormal attitude towards food that causes someone to change their eating habits and behaviour. People with an eating disorder may focus excessively on their weight and shape, leading them to make unhealthy choices about food with damaging results to their health, emotions, and ability to function in important areas of life. This study aimed to investigate the prevalence of eating disorders and its associated factors among female going-school adolescents in Jeddah, Saudi Arabia. Methods: A cross-sectional study was conducted in five schools in Jeddah, Saudi Arabia, among 554 female adolescent students from age 13 to age 18. Students with physical and psychological disabilities, were excluded from this study. A stratified random sampling technique and proportional stratified sampling technique (PSS) were used to select the participants. Data was collected via an online selfadministered questionnaire including Eating Attitudes Test-26 (EAT-26), socio-cultural Attitudes Toward Appearance Questionnaire (SATAQ-4) and Eating Behaviours and Physical Activity Questionnaire from June to July 2021. Results: This study included 502 female school-going students with a response rate of 90.6%. Their median age was 16 (IQR 2, range 13-18 years). Most of the participants were Saudi (90.8%). Most fathers (44.2%) have undergraduate degrees or higher education levels, while most mothers (38.4%) have high school education levels. Among the participants, 47.8% have a moderate household monthly income (5000-14999 Saudi Riyal). Most of the participants (65.1%) were from secondary grade, and the prevalence of eating disorders was 53.6% (n=269). Their median (IQR) EAT-26 score for participants was 21 (IQR 22). Around 45% of the participants had family influences, 36.7% had peer influences, and 49.4% had media influences on their appearance and body shape. Family influences and food habits were significantly associated with the eating disorders (p<0.05). Conclusion: this study established that more than 50 % of female school-going students were found to have eating disorders. The high prevalence of eating disorders among schoolgirls in Jeddah, Saudi Arabia, is of great concern. In order to mitigate these problems, effective programs must be designed to change dietary habits while considering the effects of family, peer and media influence, as well as focusing on the importance of breakfast and practicing physical activity.